(untitled) (Journal of Parents and Teachers, 2014)
The human being is in danger of being subjected to psychological autism or, on the contrary, to an alienated existence. Therefore, in order to know ourselves better and not fall into either of the two dangers, it is essential to make a journey of introspection. The following article gives us a few tips on how to do this.